Proceedings of the 2013 Conference on Computer Supported Cooperative Work 2013
DOI: 10.1145/2441776.2441930
|View full text |Cite
|
Sign up to set email alerts
|

Trend makers and trend spotters in a mobile application

Abstract: Media marketers and researchers have shown great interestin what becomes a trend within social media sites. Their interests have focused on analyzing the items that become trends, and done so in the context of Youtube, Twitter, and Foursquare. Here we move away from these three platforms and consider a new mobile social-networking application with which users share pictures of "cool" things they find in the real-world. Besides, we shift focus from items to people. Specifically, we focus on those who generate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This talk will show that, as online platforms become mature, the social behavior we have evolved over thousands of years is reflected on our actions on the web as well. It turns out that, in the context of social influence, finding the "(special) many" (of those who are able to spot trends early one) is more important than trying to find the "special few" [10]; that people with different personality traits take on different roles on both Twitter and Facebook [5,6]; that language, with its vocabulary and prescribed ways of communicating, is a symbolic resource that can be used on its own to influence others [4]; and that a Facebook relationship is more likely to break if it is not embedded in the same social circle, if it is between two people whose ages differ, and if one of the two is neurotic or introvert [3]. Interestingly, we also found that a relationship with a common female friend is more robust than that with a common male friend.…”
mentioning
confidence: 99%
“…This talk will show that, as online platforms become mature, the social behavior we have evolved over thousands of years is reflected on our actions on the web as well. It turns out that, in the context of social influence, finding the "(special) many" (of those who are able to spot trends early one) is more important than trying to find the "special few" [10]; that people with different personality traits take on different roles on both Twitter and Facebook [5,6]; that language, with its vocabulary and prescribed ways of communicating, is a symbolic resource that can be used on its own to influence others [4]; and that a Facebook relationship is more likely to break if it is not embedded in the same social circle, if it is between two people whose ages differ, and if one of the two is neurotic or introvert [3]. Interestingly, we also found that a relationship with a common female friend is more robust than that with a common male friend.…”
mentioning
confidence: 99%